Modern Methods And Priorities For The Development Of The Field Of Forensic Transport Research Expertise - Yuldashev Laziz Olimovich (Genius Journals, 2024)
To develop the field of judicial transport expert examination, to increase the expertise of experts, to provide citizens with clear, reliable and transparent information on the field, to inform about the content and procedure of transport expert examination
Keywords: Forensic transport expertise; auto technical expertise; reproducibility